2018
DOI: 10.1021/acs.biomac.7b01636
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable PBAT/PLA Blend with Bioactive MCPA-PHBV Conjugate Suppresses Weed Growth

Abstract: The herbicide 2-methyl-4-chlorophenoxyacetic acid (MCPA) conjugated with poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) was prepared via a melt transesterification route. The resultant bioactive oligomer was then mixed with a blend of polylactide (PLA) and poly(butylene adipate-co-terephthalate) (PBAT) with different loadings to manufacture films to be used as a bioactive, biodegradable mulch to deliver the herbicide to target broadleaf weed species. The biological targeting of the MCPA-PHBV conjugate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…The films showed better mechanical properties with the addition of CaCO 3 , and highly orientated amorphous structures were obtained, leading to low water absorption and low degradability in the simulated soil. The herbicide 2‐methyl‐4‐chlorophenoxyacetic acid (MCPA) conjugated with poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV) was prepared by Kwiecien et al via a melt transesterification route. The resultant bioactive oligomer was then mixed with PLA and PBAT to be used as a bioactive, biodegradable mulch to deliver the herbicide to target broadleaf weed species.…”
Section: Introductionmentioning
confidence: 99%
“…The films showed better mechanical properties with the addition of CaCO 3 , and highly orientated amorphous structures were obtained, leading to low water absorption and low degradability in the simulated soil. The herbicide 2‐methyl‐4‐chlorophenoxyacetic acid (MCPA) conjugated with poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV) was prepared by Kwiecien et al via a melt transesterification route. The resultant bioactive oligomer was then mixed with PLA and PBAT to be used as a bioactive, biodegradable mulch to deliver the herbicide to target broadleaf weed species.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen from the EDS data depicted in Figure 2 that the quantity of the signature element Cl correlates well with the concentration of MCPA used to coat the bioactive mulch film and that it is absent in the negative control, as previously reported. 26 Furthermore, the results from the EDS analysis performed after the greenhouse experiments indicate that the quantity of signature element Cl has decreased substantially in all the mulch film samples coated with MCPA. Overall, the trend in the results correlates with the initial concentration of MCPA present on the bioactive films ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 95%
“…In this regard, the results of our preliminary study on the application of biodegradable mulch for the control of broad leaf weed species indicated that MCPA-PHBV conjugate suppressed weed growth. 26 However, the main limitation of this pilot study was the relatively large range of MCPA levels tested, against limited broadleaf weed species, which germinated as a result of natural soil infestation. The current study is a follow-up to our previous investigation and has been meticulously designed to examine a narrower range of herbicide MCPA levels embedded within the biodegradable bioactive films, against a wider variety of broadleaf species, using artificial weed infestation of soil media.…”
Section: Introductionmentioning
confidence: 98%
“…Currently, biodegradable mulching films attract growing interest in weed management as an alternative to conventional polyethylene‐based ones . Kwiecien et al .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, biodegradable mulching films attract growing interest in weed management as an alternative to conventional polyethylene‐based ones . Kwiecien et al . demonstrated that a conjugate of herbicide 2‐methyl‐4‐chlorophenoxyacetic acid and poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) immobilized in a biodegradable poly(butylene adipate‐co‐terephthalate) (PBTA)/polylactide (PLA) blend may be gradually released at a sufficient level to supress the growth of broadleaf weed species.…”
Section: Introductionmentioning
confidence: 99%